Tropical sea cucumber fisheries: Changes during the last decade. (August 2018) - Conand, Chantal
Abstract: Tropical sea cucumber fisheries are generally traditional, small-scale, multispecies and poorly managed. Many recent studies have improved our knowledge on the biology and ecology of the commercially important species; the main results are analysed and the remaining gaps discussed. The fisheries and the patterns of trade changes during the last decade are presented from the data available and confirm overexploitation in the traditional Indian Ocean and West Pacific countries and territories. Several Latino-American countries now have active fisheries. Despite the management and conservation issues which have recently received more attention at international, regional and national levels, more measures are still needed at all these levels, to ensure sustainable exploitations of these resources. Highlights: Tropical holothurians: details on recent advances in biology and ecology of the commercial species. Changes during the last decade in the tropical fisheries: more countries, more species, more medium and low value species. Changes during the last decade in the main Chinese markets. Management options and conservation issues at the international, regional and national levels; remaining gaps.